Histological, Transcriptomic, and Functional Analyses Reveal the Role of Gibberellin in Bulbil Development in Lilium lancifolium - Shanshan Du; Mengdi Wang; Jiahui Liang; Wenqiang Pan; Qianzi Sang; Yanfang Ma; Mengzhu Jin; Mingfang Zhang; Xiuhai Zhang; Yunpeng Du (Plants)
Lily bulbils, advantageous axillary organs used for asexual reproduction, have an underexplored developmental mechanism. Gibberellins are known to participate in bulbil development, but the regulatory mechanisms remain unclear. In this study, exogenous gibberellin (GA3) significantly increased the bulbil length, width, and weight by raising the endogenous gibberellin levels and elongating the scale cells. Transcriptomic analysis identified LlGA20ox2, a key gibberellin biosynthesis gene, which was upregulated during bulbil development and significantly responsive to GA3 treatment. Given the similarities in bulbil and bulblet development, we determined the roles of LlGA20ox2 using a bulblet system. Silencing LlGA20ox2 in bulblets inhibited development by reducing the cell length, while overexpression increased the bulblet length and width. In the gibberellin signaling pathway, we identified two key genes, LlGID1C and LlCIGR2. Silencing these genes resulted in phenotypes similar to LlGA20ox2, inhibiting bulblet development. Further transcriptomic analysis revealed that gibberellin-responsive genes were enriched in the glucuronate pathway, pentose phosphate pathway and galactose metabolism pathways. Most of these differentially expressed genes responded to gibberellin and were highly expressed in later stages of bulbil development, suggesting their involvement in gibberellin-regulated bulbil growth. In conclusion, we preliminarily explored the mechanisms of gibberellin regulation in bulbil development, offering significant commercial potential for new lily reproductive organs.